Patient-reported treatment outcomes in ME/CFS and long COVID - Martha Eckey; Peng Li; Braxton Morrison; Jonas Bergquist; Ronald W. Davis; Wenzhong Xiao (Proceedings of the National Academy of Sciences, 2025)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and long COVID are persistent multisystem illnesses affecting many patients. With no known effective FDA-approved treatments for either condition, patient-reported outcomes of treatments may prove helpful in identifying management strategies that can improve patient care and generate new avenues for research. Here, we present the results of an ME/CFS and long COVID treatment survey with responses from 3,925 patients. We assess the experiences of these patients with more than 150 treatments in conjunction with their demographics, symptoms, and comorbidities. Treatments with the greatest perceived benefits are identified. Patients with each condition who participated in the study shared similar symptom profiles, including all the core symptoms of ME/CFS, e.g., 89.7% of ME/CFS and 79.4% of long COVID reported postexertional malaise (PEM). Furthermore, treatment responses between these two patient groups were significantly correlated (R 2 = 0.68). Patient subgroups, characterized by distinct symptom profiles and comorbidities, exhibited increased responses to specific treatments, e.g., a POTS-dominant cluster benefiting from autonomic modulators and a cognitive-dysfunction cluster from CNS stimulants. This study underscores the symptomatic and therapeutic similarities between ME/CFS and long COVID and highlights the commonalities and nuanced complexities of infection-associated chronic diseases and related conditions. While this study does not provide recommendations for specific therapies, in the absence of approved treatments, insights from patient-reported experiences provide urgently needed real-world evidence for developing targeted patient care therapies and future clinical trials.